Auditory Modulation of Somatosensory Spatial Judgments in Various Body Regions and Locations - Yukiomi Nozoe; Kaoru Sekiyama; Wataru Teramoto (i-Perception, 2011)
The spatial modulation effect has been reported in somatosensory spatial judgments when the task-irrelevant auditory stimuli are given from the opposite direction. Two experiments examined how the spatial modulation effect on somatosensory spatial judgments is altered in various body regions and their spatial locations. In experiment 1, air-puffs were presented randomly to either the left or right cheeks, hands (palm versus back) and knees while auditory stimuli were presented from just behind ear on either the same or opposite side. In experiment 2, air-puffs were presented to hands which were aside of cheeks or placed on the knees. The participants were instructed to make speeded discrimination responses regarding the side (left versus right) of the somatosensory targets by using two footpedals. In all conditions, reaction times significantry increased when the irrelevant stimuli were presented from the opposite side rather than from the same side. We found that the back of the hands were more influenced by incongruent auditory stimuli than cheeks, knees and palms, and that the hands were more influenced by incongruent auditory stimuli when placed at the side of cheeks than on the knees. These results indicate that the auditory-somatosensory interaction differs in various body regions and their spatial locations.